Analysis of temperature and pressure distribution in brake disc for regenerative braking - Sarip, Shamsul
A brake which is designed to provide a limited proportion of the total braking force at normal decelerations may be able to brake the car at high decelerations but may suffer damage when used for emergency braking. A conventional braking system uses 100% of friction braking to retard a moving car while with regenerative braking the friction brakes will supply less than 100%. This paper starts to establish the working limitations of lightweight brakes for regenerative braking in extreme deceleration. Thermo-mechanical analysis can be used to predict the temperature profile on disc surfaces and analytical and experimental methods can be used to predict the thermal braking performance to calculate temperature rises under emergency braking conditions and brake cooling. The aim is to establish an analytical and experimental procedure to design a lightweight disc rotor for general use at high duty levels.